(untitled) (Journal of Hama University, 2022)
This research aimed to determine the role of e-marketing in the development of small projects, specifically targeting handicraft projects, by studying the role of e-promotional tools as one of the elements of the marketing mix, namely: the website, social media platforms, e-mail, marketing through search engines. In the development of these projects compared to traditional marketing, the researcher relied on the descriptive analytical approach as a general approach to research, where a questionnaire was designed and distributed to an intentional sample (100, which retrieved 70 valid questionnaires for statistical analysis) from handicraft projects, and the researcher used the statistical program Spss to perform the characterization Statistical and hypothesis testing. The research found a positive moral effect of e-marketing in the development of handicraft projects, and the arrangement of electronic promotion tools in terms of the strength of influence on the development of the projects in question, according to the following order: social media platforms, website, e-mail, search engines, and the researcher provided an explanation for these results.